Easy Communication System as A Mediation of The Influence of Whatsapp Business on Consumer Purchase Intention on The Marketplace - Wisnalmawati, Wisnalmawati; Aribowo, Agus Sasmito; Herawati, Yunie (RSF Conference Series: Business, Management and Social Sciences, 2021)
Marketing using social media is a necessity in the era of industrial technology 4.0. This research problem is a business phenomenon and gap research. The purpose of this study is to analyze; 1. the direct influence of business WhatsApp on purchase intention in the marketplace. 2. the influence of business WhatsApp on the ease of communication system in the marketplace. Three, the influence of the ease of communication system on consumer purchase intentions in the marketplace. 4. the influence of business WhatsApp on purchase intentions on the marketplace mediated by the ease of communication systems on the marketplace The unit of analysis of this research is Sri Rejeki, and Seruni SMEs, a sample of 60 consumers, accidental sampling technique, data collection using a questionnaire (google form), testing the validity and reliability of indicator statement items, data analysis technique used is path analysis with the SPSS program. The results show that WhatsApp Bisnis has no direct and insignificant effect on consumers’ purchase intentions. WhatsApp Business has a positive and significant effect on the ease of system communication has a positive and significant effect on consumer purchase intentions. WhatsApp Business has a positive and significant effect on consumer purchase intentions mediated by the ease of communication system. The novelty of this research is to create an ease of communication system to increase consumer purchase intentions in the marketplace. Ease of communication is a mediation between the influence of WhatsApp business on purchase intentions on the marketplace so that the ease of communication is an important variable that needs to be improved so that consumers intend to use the marketplace in purchasing products. The ease of communication is related to the ease of using the application, the ease of alternative transactions, and the design of a simple order form. This is hope for consumers to use the marketplace. Contribution of marketplace training to MSMEs and community business actors.